Cosmopolitanism or Multiculturalism? Towards an Anti-Colonial Reading - Sefa Dei, George J. (International Journal for Talent Development and Creativity)

(untitled) (International Centre for Innovation in Education/Lost Prizes International, 2022)
Using Multiculturalism as an entry point, the paper interrogates conventional ideas and themes of Cosmopolitanism from an anti-racist and anti-colonial read. The discussion is informed by how the anti-racist and anti-colonial lens has shaped an understanding of multiculturalism and its convergences and divergences with Cosmopolitanism. My goal is to advance a rethinking' cosmopolitanism' from an Indigenist anti-colonial democratic lens highlighting a philosophy of educational practice geared towards new educational futurities for particularly [but not exclusively] Black, Indigenous and racialized bodies in the school system. It is argued that cosmopolitanism is about Land and relationships. This offers possibilities of learning from the ‘geographies of schooling’. The pedagogies of the Land, for example, require examining the narratives and encounters taking place in these 'geographies of schooling' to unravel colonial structures of education and ways we validate contending or competing for multiple knowledges for decolonizing and anti-colonizing education. In the context of the cosmopolitan, institutions like schools, as carceral projects, must acknowledge that anti-Black racism is ‘pervasive throughout the system’ and not simply assert rhetorically that 'anti-Black racism has no place in our school'! Critical educators in their practice of teaching training and preparation, must be able to name institutional silences, erasures, negligence, and complicities around race, anti-Black racism, and Indigeneity in order to create inclusive learning communities and schools as ‘working communities’.